Repair Rate and Durability of Video Assisted Minimally Invasive Mitral Valve Surgery. Issue 6 (25th August 2014) - Reser, Diana; van Hemelrijck, Mathias; Pavicevic, Jovana; Platzmann, Anna; Caliskan, Etem; Falk, Volkmar; Jacobs, Stephan
Abstract: Background: Minimally invasive mitral valve surgery (MIMVS) through a right lateral thoracotomy has emerged as another option in cardiac surgery. We present our single center experience with regards to repair rate and durability of the repair in patients undergoing MIMVS. Methods: Between January 2009 and December 2012 a total of 312 consecutive patients underwent MIMVS. Baseline characteristics, operative variables, postoperative outcomes, and follow‐up information about survival, major adverse cardiac and cerebrovascular event (MACCE)‐free survival, valve competence, and freedom from reoperation were collected. Results: Mean age was 61 ± 13.1 years, median Euroscore 4 (0–13). The predominant valve pathology was degenerative disease (96.2%) with regurgitation (95.2%) and atrial fibrillation (23.1%). Bypass time was 147 ± 46, cross‐clamp time 94 ± 32 minutes. All degenerative valves planned for repair (n = 281) were successfully repaired except for two (0.7%) resulting in a 99.3% repair rate. Eight patients (2.8%) had to be converted to sternotomy. Median ventilation time was 6.6 hours (0 to 460), ICU stay one day (0 to 96), and hospital stay eight days (3 to 61). Most of the patients did not need red blood cell transfusion (78.2%). One patient died in hospital due to acute respiratory distress syndrome (0.3%) and five suffered a permanent stroke (1.6%). In 294 patients (94.5%) follow‐up was completed for a median of 22 months (0 to 53) with 95.5 ± 1.2% overall survival, 96.8 ± 1.2%, MACCE‐free survival, and 94.8 ± 0.1% freedom from reoperation. Conclusions: MIMVS is a safe approach with low morbidity and mortality that allows a high and durable repair rate with low reoperation rates and favorable short‐term event‐free survival. doi: 10.1111/jocs.12439 (J Card Surg 2014;29:766–771)